Compatibilization of an architectural and hydrossanitary project using the BIM methodology (Research, Society and Development, 2021)
The presence of incompatibilities in hydrosanitary projects is frequent in the traditional 2D project. With the evolution of the civil construction market and a demand for optimized projects, work methods need to stay updated. Therefore, a way to integrate the professionals involved in the construction life cycle is through the Building Information Modeling (BIM). It allows the visualization of the building before construction, permitting an interference check and promoting efficient solutions. However, BIM hasn’t been implemented in Brazil yet, having many companies in the initial phase of its adoption and few practical studies about the methodology in the area of cold water and sewer projects. So, the objective of this paper was to verify the applicability of the BIM methodology in 3D modeling of a hydrosanitary project. Thus, the architectural project was reproduced with the cold water and sewer project in Revit, seeking incompatibilities. After solving them, sections, views and quantities were generated, from which an analysis of automation and the impacts caused by conflicts was made. At the end of the study, BIM's efficiency with regard to automation for doing interdisciplinary projects was observed, in addition to offering better dynamism to the planning of the work and reducing rework.